Ambient air pollution, bone mineral density and osteoporosis: Results from a national population-based cohort study. (January 2023) - Yang, Yin; Li, Rui; Cai, Miao; Wang, Xiaojie; Li, Haopeng; Wu, Yinglin; Chen, Lan; Zou, Hongtao; Zhang, Zilong; Li, Haitao; Lin, Hualiang
Abstract: Evidence concerning the associations of ambient air pollution exposure with bone mineral density and osteoporosis has been mixed. We conducted cross-sectional and prospective analysis of the associations between air pollution exposure and osteoporosis using data from UK Biobank study. Estimated bone mineral density (eBMD) of each participant at baseline survey was calculated using quantitative ultrasound data, and incident osteoporosis cases were identified during the follow-up period according to health-related records. Air pollution concentrations were assessed using land use regression models. We fitted multivariable linear and logistic regression models to estimate the associations of air pollution with eBMD and osteoporosis prevalence at baseline. We applied cox proportional hazard regression models to assess the relationships between air pollution and osteoporosis incidence. Among the 341, 311 participants at baseline, higher air pollution exposure was associated with lower eBMD levels and increased odds of osteoporosis prevalence. For example, an IQR increase in PM2.5, PM2.5 absorbance, PM10, NO2 and NOx levels were associated with 0.0018 (95% CI: 0.0012, 0.0023) to 0.0052 (95% CI: 0.0046, 0.0058) g/cm 2 decrease in eBMD. A total of 330, 988 participants without osteoporosis were followed up for an average of 12.0 years. We identified 8105 incident osteoporosis cases (456 cases with pathological fracture and 7634 cases without pathological fracture) during the follow-up. The hazard ratios for an interquartile range increase in PM2.5, PM2.5 absorbance, PM10, NO2 and NOx were 1.09 (95% CI: 1.06, 1.12), 1.04 (95% CI: 1.02, 1.07), 1.04 (95% CI: 1.01, 1.07), 1.07 (95% CI: 1.04, 1.10), and 1.06 (95% CI: 1.03, 1.09), respectively. Our study suggests that ambient air pollution might be a risk factor of decreased bone mineral density and osteoporosis incidence. Graphical abstract: Image 1 Highlights: We conducted analysis using data from 341, 311 participants in the UK Biobank. Long-term exposure to PMs, NO2 and NOx was associated with lowered bone mineral density. Long-term exposure to PMs, NO2 and NOx increased the risk of osteoporosis incidence.